2017
DOI: 10.1016/j.sleep.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in women undergoing in vitro fertilization: a pilot study

Abstract: Objective Sleep disturbances are thought to be frequent in women undergoing IVF despite minimal research of this hypothesis. Our goal was to longitudinally assess sleep duration and disturbances in women undergoing IVF and assess impact of habitual sleep duration on oocytes retrieved, an important outcome in IVF. Methods Actigraphy and questionnaire batteries containing sleep and psychometric instruments were performed prior to and throughout 24 IVF cycles. Results TST <7 hours was present in 46%, 57%, 69%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 79 publications
(85 reference statements)
3
39
0
4
Order By: Relevance
“…The present study builds on research conducted among populations with known fertility impairments such as PCOS or diagnosed infertility. Although these studies differ methodologically, our findings agree with cross-sectional studies showing associations between infertility and impaired sleep, including hours of sleep, quality of sleep, and sleep disorders (12)(13)(14)(15)30).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study builds on research conducted among populations with known fertility impairments such as PCOS or diagnosed infertility. Although these studies differ methodologically, our findings agree with cross-sectional studies showing associations between infertility and impaired sleep, including hours of sleep, quality of sleep, and sleep disorders (12)(13)(14)(15)30).…”
Section: Discussionsupporting
confidence: 89%
“…In an infertility clinic study population, disturbed sleep was associated with diminished ovarian reserve as measured by follicle-stimulating hormone (FSH), estradiol, inhibin B, and M€ ullerian-inhibiting substance, although the temporality of the association was unclear (14). In a study of women undergoing in vitro fertilization (IVF), the number of oocytes retrieved was positively associated with actigraphmeasured sleep time (15).…”
mentioning
confidence: 99%
“…For this reason, in the MIART trial (Fernando et al , 2014), we chose to examine administration BD in this dose-finding study, aiming to determine whether melatonin given in such a dosing regimen might improve IVF outcomes. As an a priori determined outcome, we also wished to explore the effect of such BD melatonin on sleep and daytime sleepiness because any beneficial effect on sleep in infertile women is likely to have a positive impact on patients (Goldstein et al , 2017) and any negative effects on sleep quality or daytime sleepiness may restrict its use in future clinical trials, in this and other medical disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbance may interfere with fertility through effects on the hypothalamic–pituitary axis and gonadotrophin regulation (Kloss et al , 2015) or on immunity (Vgontzas et al , 2004; Irwin et al , 2006). It has also been hypothesized that sleep disturbance may have a negative effect on IVF outcomes (Goldstein et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, polymorphisms of clock genes are present in the peripheral blood of women with recurrent pregnancy losses 10 . Objective (actigraphy and light exposure) and subjective (questionnaires) measures of sleep in women with mixed causes of subfertility undergoing in vitro fertilization has previously shown that there is a trend towards an association between length of sleep and number of oocytes retrieved 11 . However, total sleep time and the quality of sleep are likely to be influenced by medical process, and have not been compared outside a treatment setting, nor compared with a comparison group of fertile women.…”
Section: Introductionmentioning
confidence: 99%